A study on impact of climate change on horticulture sector in Jammu and Kashmir: an economic overview - Dr Prabha Bhatt, Mohmmad Younus Wani, (International Journal of Scientific Research and Management (IJSRM), 2017)
Climate plays an important role for every type of sector, especially in agriculture. Climate threat increases from various interactions between environments, economic, social, religious and political systems. The livelihood of the society can be badly affected directly or indirectly due to the climatic changes. Horticulture is the backbone of Jammu and Kashmir and majority of the population getting their livelihood through this sector. The researcher attempted to study the effect of horticulture crops such as apple, walnut and saffron due to various climatic risks. Recently examples of the state were the flood damage by heavy rainfall in 2014and dry weather in 2016. In the latest induction of climate change an unpredicted hailstorm compiled with untimely rain has damaged the crop and causing loss of 2 billion rupees. The floods of 2014 make the destruction of major crops like, apple, pear, walnut, saffron, cherry etc. and causes loss of over 14.25 billion rupees. For the last many years the production of saffron is decreasing at high level, in 2015 the saffron production was below average. The less precipitation and high temperature records from last many years has damaged the crops, mostly apple, saffron and walnut and at the same time has caused diseases like scab, red might etc. that damages the fruits. Due to high weather and humidity the insect and germs like bacteria, fungus, algae grows more and affects the fruits. Due to low rainfall the growth and colour remain slow as in apple and saffron which results in the low price and also reduces its taste.